Oroxylin A prevents alcohol-induced hepatic steatosis through inhibition of hypoxia inducible factor 1alpha. (1st April 2018) - Jin, Huanhuan; Lian, Naqi; Bian, Mianli; Zhang, Chenxi; Chen, Xingran; Shao, Jiangjuan; Wu, Li; Chen, Anping; Guo, Qinglong; Zhang, Feng; Zheng, Shizhong
Abstract: Accumulating data reveal that oroxylin A has beneficial effects against chronic liver disease. The previously studies showed oroxylin A, a flavonoid extracted from Scutellariae radix, improved acute liver injury and accelerated liver regeneration in vivo . However, it's unclear that the effect of oroxylin A on alcoholic liver disease. The present study was aimed at elucidating the effect of oroxylin A on alcohol-induced hepatic steatosis and the underlying mechanisms. Human hepatocyte LO2 were cultured and stimulated with ethanol for inducing LO2 damage. We examined the effects of oroxylin A on the accumulation of lipid droplets in ethanol-treated LO2 . The results showed that oroxylin A reduced the accumulation of lipid droplets associated with regulating the lipid metabolism genes. Moreover, oroxylin A significantly suppressed the nuclear translocation of HIF-1α in ethanol-treated LO2 . Furthermore, activation of HIF-1α significantly attenuated the effect of oroxylin A on lipid droplets accumulation and genes related to lipid metabolism in vitro and in vivo . Altogether, we demonstrated a HIF-1α-associated mechanism underlying oroxylin A inhibition of lipid deposition in ethanol-stimulated LO2 . Oroxylin A modulation of HIF-1α level may represent a therapeutic remedy for ALD. Graphical abstract: Highlights: Oroxylin A inhibited lipid accumulation and regulated the genes of hepatic lipid metabolism in ethanol-treated LO2 . Interference of HIF-1α is required for oroxylin A reduction of ethanol-induced lipid accumulation in vitro. Oroxylin A ameliorated ethanol-induced hepatic steatosis and inflammation through inhibiting HIF-1α in vivo .